Desain Kinerja Guru Dalam Menciptakan Lingkungan Belajar Yang Berorientasi Paikem Bagi Siswa - Haposan Simanjuntak; Lasmon Sitompul; Victoria Sinaga; Winda Sari Rumahorb; Novita Ester Marlina Zebua; Titin Aritonan (Departement of Mathematics Education, 2024)
Education is a forum for seeking knowledge for everyone and this knowledge must be achieved according to the target. Educational stages start from elementary school, middle school, vocational school to college. Education can be achieved if the learning process provides a pleasant atmosphere for students, so that learning can be carried out actively, creatively and innovatively. However, in the learning process many things are found that students do not enjoy an active, innovative, creative, effective and fun classroom atmosphere, in fact they are bored, fed up, have difficulty capturing learning and are less enthusiastic about learning. It is the duty of a teacher to have the ability or strategy to take responsibility for his profession as an educator, teacher, facilitator and motivator, so that he can overcome problems like this for students, so that they can experience an active, innovative, creative, effective learning process. and fun (PAIKEM). The aim of this writing is to find out the teacher's strategy or design in realizing a PAIKEM classroom atmosphere for his students, which then makes it easier for them to achieve maximum education through the design carried out by the teacher. The method used by the author is a qualitative method with an approach to literature or literature studies sourced from journals, books, websites and other online media that can be academically accountable. The result of this paper is that a teacher can have the ability to design learning or strategies that lead to PAIKEM to be applied to students in the teaching and learning process, so as to create a classroom environment that is oriented towards PAIKEM.